Device and method for testing hydrogen diffusion coefficient of high-strength steel
By using scanning Kelvin probe technology in the hydrogen diffusion coefficient test device of high-strength steel, in-situ and real-time detection of hydrogen diffusion behavior of high-strength steel is achieved, the problem of lack of lateral resolution in the existing methods is solved, and an efficient method for measuring hydrogen diffusion coefficient is provided.
Patent Information
- Application Number
- CN202510014499.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-28
AI Technical Summary
The existing Devanathan-Stachurski dual electrolytic cell electrochemical hydrogen permeability method cannot effectively detect local hydrogen concentration and distribution in high-strength steels, and lack of lateral resolution, resulting in the detection results of hydrogen flux may be underestimated.
A high-strength steel hydrogen diffusion coefficient test device and method based on scanning Kelvin probe (SKP) technology was designed. By detecting hydrogen flux in situ and real-time, combined with electrochemical hydrogen charging and synchronous use with SKP technology, visual measurement of the hydrogen diffusion coefficient of high-strength steel is achieved.
This method can effectively detect the hydrogen diffusion behavior in high-strength steel, provide test results with high lateral resolution, solve the problem of lack of lateral resolution in existing methods, and provides a scientific basis for evaluating the hydrogen embrittlement sensitivity and reliability of high-strength steel.
Smart Images

Figure CN119715349A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the technical field of corrosion electrochemical testing, and in particular relates to a high-strength steel hydrogen diffusion coefficient testing device and method, which are used for in-situ measuring the potential change of the high-strength steel surface after hydrogen is charged. Background technology:
[0002] With the development of modern industry, the requirements for material performance are getting higher and higher. For example, the lightweight of automobiles, deep-sea development of oceans, and the ultra-long life of bridges have put forward higher requirements for the strength of steel. Many countries attach great importance to the development of high-strength steel. Japan, South Korea and China have invested heavily in the implementation of the "Super Steel Plan", "High-Performance Structural Steel Plan" and "Major Basic Research on New Generation Steel Materials". The research and development of high-strength steel is an important research topic. However, the higher the strength of steel, the higher the sensitivity to hydrogen. Even a very small amount of hydrogen can cause delayed fracture of high-strength steel. Based on this, it is particularly important to evaluate the sensitivity of materials to hydrogen embrittlement to ensure the reliability and safety of high-strength steel during service. In addition to the material factors of the steel itself, the occurrence of hydrogen embrittlement of high-strength steel is considered to be the main cause of hydrogen embrittlement due to the absorbed diffuse hydrogen (environmental factors). For example, the diffuse hydrogen generated by corrosion and cathodic protection during the application of high-strength steel materials.
[0003] Electrochemical hydrogen permeation is the most commonly used method to test and evaluate the permeation and diffusion behavior of hydrogen in steel materials. It uses the Devanathan-Stachurskis double electrolytic cell to measure the macroscopic hydrogen diffusion of the material, which is suitable for studying the factors that affect the hydrogen diffusion coefficient of the material. For example, Huang Yanliang et al. used the Devanathan-Stachurski hydrogen permeation technology to study the hydrogen permeation behavior of three materials, 16Mn, X56 and 35CrMo, in the marine atmospheric environment; Sun Yongwei used the Devanathan-Stachurski double electrolytic cell permeation device to measure the hydrogen diffusion coefficients of 40CrNiMoA, 0Cr16Ni5Mo and 12CrNi9MoV steels, typical high-strength bolt materials for marine engineering, to evaluate the time and enrichment degree of hydrogen in the steel to reach equilibrium; Ke Shuzhong combined the Devanathan-Stachurski double electrolytic cell hydrogen permeation test and slow strain rate tensile test to measure the hydrogen embrittlement sensitivity and hydrogen permeation behavior of DP600 steel; Yang Chaofei et al. used the double electrolytic cell electrochemical hydrogen permeation test method to determine the hydrogen diffusion coefficients of three low-alloy high-strength steels at different temperatures and different tensile stresses, and established a unified equation for the hydrogen diffusion coefficient of low-alloy high-strength steel; Du et al. used the Devanathan-Stachurski double electrolytic cell technology for hydrogen permeation experiments and reported the hydrogen permeation and hydrogen damage behavior of high-strength casing steel in an acidic environment. The above studies show that the higher the strength of steel, the higher the hydrogen diffusion coefficient, the higher the diffusible hydrogen concentration, and the higher the hydrogen embrittlement sensitivity. The Devanathan-Stachurski double-electrolytic cell electrochemical hydrogen permeation method measures the macroscopic hydrogen diffusion of the material by pre-electroplating Pd and Ni on the surface of the sample. However, it cannot characterize the local hydrogen concentration and distribution in the steel, and the detection of hydrogen flux requires an electrochemical hydrogen charging reaction on the surface of the steel material first. The test results lack lateral resolution, resulting in the averaging of the hydrogen flux from the test area. Therefore, local hydrogen flux or sub-surface hydrogen concentration cannot be detected by this method and may be underestimated.
[0004] The scanning Kelvin probe (SKP) technique can detect the hydrogen flux generated by metal materials under corrosion conditions in situ and in real time. Compared with the electrochemical hydrogen permeation method, it has high sensitivity, does not require Pd and Ni to be electroplated on the sample surface in advance, and can visualize the diffusion behavior of hydrogen with a certain lateral resolution.
[0005] Therefore, a testing device and method for the hydrogen diffusion coefficient of high-strength steel was developed and designed. Based on the scanning Kelvin probe technology, the hydrogen diffusion coefficient of high-strength steel after electrochemical hydrogen charging can be quickly determined. Summary of the invention:
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art, develop and design a high-strength steel hydrogen diffusion coefficient testing device and method, observe the diffusion behavior of hydrogen based on a visual method, and display the lateral resolution.
[0007] In order to achieve the above-mentioned purpose, the main structure of the high-strength steel hydrogen diffusion coefficient testing device of the present invention includes an electrolytic cell and a circulating water interface arranged at its bottom, a platinum electrode and a reference electrode arranged at the top, an inner cover plate and an outer cover plate arranged at the top, and a sample arranged between the inner cover plate and the outer cover plate; wherein:
[0008] The electrolytic cell and the circulating water interface are connected through a threaded interface arranged on the side of the electrolytic cell and a circulating water interface nut arranged at the end of the circulating water interface, and a gasket is arranged between the threaded interface and the circulating water interface nut;
[0009] The platinum electrode is coaxially arranged with the reference electrode, one end of which extends to the inside of the electrolytic cell and the other end of which extends to the outside of the electrolytic cell;
[0010] A through hole is opened at the center of the inner cover plate, and a sealing ring is arranged at the through hole;
[0011] The outer cover plate is connected to the electrolytic cell by bolts.
[0012] The specific process of using the high-strength steel hydrogen diffusion coefficient testing device of the present invention comprises the following steps:
[0013] (1) Installation
[0014] First, a high-strength steel specimen was placed between the inner cover plate and the outer cover plate;
[0015] Then, the outer cover plate is fixedly connected to the electrolytic cell;
[0016] Finally, the platinum electrode, reference electrode and high-strength steel sample were connected to the electrochemical workstation respectively;
[0017] (2) Hydrogen charging
[0018] Invert the electrolytic cell, add NaCl electrolyte solution into the electrolytic cell, set the hydrogen charging parameters and then charge the cell with hydrogen;
[0019] (3) Measurement
[0020] First, pour out the NaCl electrolyte solution immediately after hydrogen charging is completed and place the electrolytic cell upright;
[0021] Then, the surface of the high-strength steel sample that is not filled with hydrogen is connected to the scanning Kelvin probe, the sample surface is leveled with a level, the probe is moved to the center of the hydrogen-filled area, and then the probe is moved 15-20 mm to the left, the distance between the probe and the sample surface is adjusted to 100 μm, and the line scanning measurement mode of the SKP equipment is started to perform potential measurement;
[0022] Finally, the potential of the high-strength steel samples was measured at different times, and the change of potential with time was recorded.
[0023] The high-strength steel sample of the present invention is ground and polished before installation;
[0024] The current density of hydrogen charging is set to 0.5-5mA / cm 2 , hydrogen filling time is 0.5-3h;
[0025] Based on the measurement results, the relationship between the diffusion distance of hydrogen and the potential at different diffusion times and the hydrogen diffusion coefficient of the high-strength steel sample can be analyzed.
[0026] Compared with the prior art, the present invention does not require pre-plating on the surface of the high-strength steel sample, thereby avoiding heavy metal pollution. At the same time, after the electrochemical hydrogen charging is completed, the in-situ SKP potential measurement is carried out in combination with the scanning Kelvin probe technology. Based on the measurement results, the hydrogen diffusion coefficient of the in-situ high-strength steel can be obtained through calculation and analysis. The test result has a certain lateral resolution, which solves the problem of lack of lateral resolution of the Devanathan-Stachurski double electrolytic cell electrochemical hydrogen permeation method, provides a scientific basis for in-depth research on the hydrogen permeation behavior of high-strength steel in the marine environment and the selection, use and maintenance of high-strength steel materials in the marine engineering field, and provides data support for ensuring the reliability and safety of high-strength steel during service. The device has a simple structure and a simple test method. It does not require pre-plating of Pd and Ni on the surface of the high-strength steel, which reduces the test cost and greatly shortens the test cycle, providing important data support and technical reference for the research and development of new high-strength steel varieties, the selection of materials for engineering structure design, and the evaluation of the service life of steel. Description of the drawings:
[0027] Figure 1 It is a schematic diagram of the main structural principle of the present invention.
[0028] Figure 2 It is an exploded view of the main structure of the present invention.
[0029] Figure 3 It is a top view of the main structure of the present invention.
[0030] Figure 4 This is a schematic diagram of the relationship between the SKP potential and the linear diffusion distance of a high-strength steel sample at different diffusion times involved in the present invention.
[0031] Figure 5 It is a schematic diagram of the linear relationship between the hydrogen diffusion distance and the diffusion time involved in the present invention. Specific implementation method:
[0032] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0033] Embodiment 1:
[0034] The main structure of a high-strength steel hydrogen diffusion coefficient testing device involved in this embodiment is as follows Figure 1-3 As shown, it includes an electrolytic cell 1, a circulating water interface 2, a platinum electrode 3, a reference electrode 4, an inner cover plate 5, an outer cover plate 6, a threaded interface 7, a circulating water interface nut 8, a gasket 9, a sealing ring 10 and a bolt 11; the electrolytic cell 1 is provided with circulating water interfaces 2 at both ends of the bottom, the platinum electrode 3 and the reference electrode 4 are provided at the front and rear sides of the upper part, and the inner cover plate 5 and the outer cover plate 6 are provided at the top, wherein:
[0035] The electrolytic cell 1 is connected to the circulating water interface 2 through a threaded interface 7 provided on the side of the electrolytic cell 1 and a circulating water interface nut 8 provided at the end of the circulating water interface 2, and a gasket 9 is provided between the threaded interface 7 and the circulating water interface nut 8;
[0036] The platinum electrode 3 is coaxially arranged with the reference electrode 4, one end of which extends to the inside of the electrolytic cell 1 and the other end of which extends to the outside of the electrolytic cell 1;
[0037] The inner cover plate 5 is embedded in the middle of the top of the electrolytic cell 1, and a through hole is opened in the center, and a sealing ring 10 is arranged at the through hole;
[0038] The outer cover plate 6 is hollowed out in the middle, and its four corners are connected to the electrolytic cell 1 by bolts 11 .
[0039] Embodiment 2:
[0040] A high-strength steel hydrogen diffusion coefficient testing method involved in this embodiment is implemented based on a high-strength steel hydrogen diffusion coefficient testing device involved in Example 1, and the specific process is as follows:
[0041] (1) Installation
[0042] First, a high-strength steel sample 100 with a size of 50 mm*50 mm*0.5 mm was ground to 1500 mesh by silicon carbide sandpaper, and then polished with 0.5 μm abrasive paste;
[0043] Then, the high-strength steel sample 100 is placed on the inner cover plate 5, and the center of the high-strength steel sample 100 is made to coincide with the center of the sealing ring 10, and then the outer cover plate 6 is placed on the high-strength steel sample 100, and the outer cover plate 6 is fixedly connected to the electrolytic cell 1 by bolts 11, wherein the size of the outer cover plate 6 is the same as the top surface size of the electrolytic cell 1, which is larger than the size of the inner cover plate 5, and the width of the high-strength steel sample 100 is larger than the length and width of the outer cover plate 6, so as to facilitate the exposure of the metal part and the wires of the electrochemical workstation for connection;
[0044] Finally, the portable electrochemical workstation is electrically connected to the platinum electrode 3, the reference electrode 4 and the high-strength steel sample 100 respectively;
[0045] (2) Hydrogen charging
[0046] First, invert the electrolytic cell 1, and adjust the opening of the water circulation interface 2 to face upwards through the circulating water interface nut 8;
[0047] Then, 0.5M NaCl electrolyte solution is added into the electrolytic cell 1 through the water circulation interface 2;
[0048] Finally, the charging parameters of the portable electrochemical workstation were set and hydrogen was charged immediately, where the current density was set to 2 mA / cm 2 , the time is set to 1h;
[0049] (3) Measurement
[0050] First, pour out the NaCl electrolyte solution immediately after hydrogen charging is completed, place the electrolytic cell 1 upright, and adjust the opening of the circulating water interface 2 to face upward;
[0051] Then, the surface of the high-strength steel sample 100 that is not charged with hydrogen (the side exposed to the atmosphere) is connected to a scanning Kelvin probe (SKP) device, the sample surface is leveled with a level, the probe is moved to the center of the hydrogen-charged area, and then the probe is moved 15-20 mm to the left, and the distance between the probe and the surface of the high-strength steel sample 100 is adjusted to 100 μm, the line scanning measurement mode of the SKP device is started, and the SKP test parameters are set to an amplitude of 30 μm, a frequency of 80 Hz, and a sensitivity of 1 mV, and potential measurement is performed;
[0052] Finally, the potential of the surface of the high-strength steel sample 100 without hydrogen charging was measured at different times (10min, 20min, 40min, 60min, 120min), and the change of the potential with time was recorded;
[0053] (4) Analysis
[0054] The SKP potential and linear diffusion distance of the non-hydrogenated surface of the high-strength steel sample 100 under different diffusion times are plotted (Ed), as shown in Figure 4 As shown, the relationship between the diffusion distance and potential of hydrogen at different diffusion times is obtained through the Ed curve;
[0055] Based on Fick's law, a graph is drawn of the hydrogen diffusion distance and the 1 / 2 power of the diffusion time, and a linear fit is performed on the graph, such as Figure 5 As shown, the hydrogen diffusion coefficient of the high-strength steel sample 100 is obtained through the fitted slope.
Claims
1. A high-strength steel hydrogen diffusion coefficient testing device, characterized in that: The main structure includes an electrolytic cell and a circulating water interface arranged at its bottom, a platinum electrode and a reference electrode arranged at the top, an inner cover plate and an outer cover plate arranged at the top, and a sample arranged between the inner cover plate and the outer cover plate.
2. A high-strength steel hydrogen diffusion coefficient testing device according to claim 1, characterized in that: The electrolytic cell and the circulating water interface are connected through a threaded interface arranged at the side of the electrolytic cell and a circulating water interface nut arranged at the end of the circulating water interface.
3. A high-strength steel hydrogen diffusion coefficient testing device according to claim 1, characterized in that: The platinum electrode is coaxially arranged with the reference electrode, one end of which extends to the inside of the electrolytic cell and the other end of which extends to the outside of the electrolytic cell.
4. The high-strength steel hydrogen diffusion coefficient testing device according to claim 1, characterized in that: A through hole is opened at the center of the inner cover plate, and a sealing ring is arranged at the through hole.
5. The high-strength steel hydrogen diffusion coefficient testing device according to claim 1, characterized in that: The outer cover plate is connected to the electrolytic cell by bolts.
6. A high-strength steel hydrogen diffusion coefficient testing device according to claim 2, characterized in that: A gasket is arranged between the threaded interface and the circulating water interface nut.
7. A method for testing the hydrogen diffusion coefficient of high-strength steel, characterized in that: The following steps are involved: (1) Installation First, a high-strength steel specimen was placed between the inner cover plate and the outer cover plate; Then, the outer cover plate is fixedly connected to the electrolytic cell; Finally, the platinum electrode, reference electrode and high-strength steel sample were connected to the electrochemical workstation respectively; (2) Hydrogen charging Invert the electrolytic cell, add NaCl electrolyte solution into the electrolytic cell, and charge hydrogen; (3) Measurement First, pour out the NaCl electrolyte solution and place the electrolytic cell upright; Then, the surface of the high-strength steel sample that is not filled with hydrogen is connected to the scanning Kelvin probe, the sample surface is leveled, the probe is moved to the center of the hydrogen-filled area, and then the probe is moved to the left, the distance between the probe and the sample surface is adjusted, and the SKP device is started to measure the potential; Finally, the potential of the high-strength steel samples was measured at different times, and the change of potential with time was recorded.
8. A method for testing hydrogen diffusion coefficient of high-strength steel according to claim 7, characterized in that: The current density of hydrogen charging is set to 0.5-5mA / cm 2 The hydrogen filling time is 0.5-3h.
Citation Information
Cited By
Method for measuring hydrogen diffusion coefficient and trap parameters of high hydrogen trap material
CN122651844A